Peran Guru Pamong dan Dosen Pembimbing Terhadap Keberhasilan Program Pengalaman Lapangan (PPL) Mahasiswa - Dasmo Dasmo; Sumaryati Sumaryati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2014)
The research was intended to proof and analyse some factors that influence the succses of field teaching program for the students of Technic Faculty, athematics and Science in University of Indraprasta PGRI. The method used in this research was survey method with multiple regresive technique. The result show that 1) there was an effect in the role of teacher and lecturer in group with average succsess 2) there was not an effect in teacher role to the success of students field teaching program, 3) there was an effect in the role of lecturer to the success of students field teaching program. Keywords: field teaching program, teacher, lecturer